2009
DOI: 10.1007/s11222-009-9128-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust mixture modeling using multivariate skew t distributions

Abstract: This paper presents a robust mixture modeling framework using the multivariate skew t distributions, an extension of the multivariate Student's t family with additional shape parameters to regulate skewness. The proposed model results in a very complicated likelihood. Two variants of Monte Carlo EM algorithms are developed to carry out maximum likelihood estimation of mixture parameters. In addition, we offer a general information-based method for obtaining the asymptotic covariance matrix of maximum likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(131 citation statements)
references
References 38 publications
0
129
0
1
Order By: Relevance
“…By design, our STNMIX model is computationally faster to fit than the skew t mixture (STMIX) model [3,12,16,17] without sacrificing precision or rigor. Ho et al [13] summarized the differences between the STMIX and STNMIX models and showed the implementation of the STNMIX model is generally much simpler and faster than that of STMIX model.…”
Section: Resultsmentioning
confidence: 99%
“…By design, our STNMIX model is computationally faster to fit than the skew t mixture (STMIX) model [3,12,16,17] without sacrificing precision or rigor. Ho et al [13] summarized the differences between the STMIX and STNMIX models and showed the implementation of the STNMIX model is generally much simpler and faster than that of STMIX model.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive details on skew-normal and skew-t distributions are given by Azzalini and Capitanio (2014). Mixtures of these formulations have been used for clustering and classification in several contexts, including work by Lin (2009Lin ( , 2010, McNicholas (2012, 2014), and McLachlan (2013a,b, 2014). Vrbik and McNicholas (2014) introduce skew-normal and skew-t analogues of the GPCM family and show that they can give superior clustering and classification performance when compared with their Gaussian counterparts.…”
Section: Mixtures Of Asymmetric Componentsmentioning
confidence: 99%
“…For example, some work has been done using symmetric component densities that parameterize concentration (tail weight), e.g., the t distribution , Andrews & McNicholas 2011, Lin, McNicholas & Hsiu 2014) and the power exponential distribution (Dang, Browne & McNicholas 2015). There has also been work on mixtures for discrete data (e.g., Karlis & Meligkotsidou 2007, Bouguila & ElGuebaly 2009) as well as several examples of mixtures of skewed distributions such as the NIG distribution (Karlis & Santourian 2009, Subedi & McNicholas 2014, the skew-t distribution (Lin 2010, Vrbik & McNicholas 2012, Lee & McLachlan 2014, 2016, the shifted asymmetric Laplace distribution (Morris & McNicholas 2013, Franczak, Browne & McNicholas 2014, the variance-gamma distribution , the generalized hyperbolic distribution , and others (e.g., Elguebaly & Bouguila 2015, Franczak, Tortora, Browne & McNicholas 2015.…”
Section: Model-based Clustering and Mixture Modelsmentioning
confidence: 99%